Efforts To Improve Learning Outcomes Of 50 Metres Short Distance Running (Sprint) Through Modification Of Playing In Grade V Students Of Tunas Harapan Elementary School - Fandy Fauzan; Imanuddin Siregar; Muhammad Badrun Siregar (Program Studi Pendidikan Jasmani Kesehatan dan Rekreasi, 2025)
The purpose of this study was to Improve the Learning Outcomes of 50-meter Sprint Short-distance Running Through Modified Play in Class V Students of SD Tunas Harapan Tanjung Anom Academic Year 2024/2025. This research method is classroom action research. The location of this research is at SD Tunas Harapan Tanjung Anom. This research was conducted in July 2024. The subjects who received the action in this study were all 34 students of Class V SD Tunas Harapan Tanjung Anom. The results of the post-test I above can be seen that the learning outcomes of students in sprint learning in athletics learning turned out that out of 34 students, there were 20 students (58.82%) who had achieved the level of learning completion, while 14 students (41.18%) had not achieved the level of learning completion in learning the 50-meter sprint short-distance running. With an average value obtained in cycle I reaching 74.26. From the data on learning outcomes in cycle II obtained, it can be seen that students' ability to carry out the 50-meter sprint short-distance running learning outcome test classically has increased. Of the 34 students, 30 students (88.23%) have achieved learning completion. Meanwhile, 4 students (11.77%) have not achieved learning completion with an average student learning outcome of 79.90. In cycle II, the teaching and learning process went well when compared to cycle I. Thus, it can be said that through the modification of play applied by the teacher, it ended in cycle II with the learning outcomes of the 50-meter sprint short distance running which were previously low to increase. The conclusion is that there was an increase in the Learning Outcomes of the 50-meter Sprint Short Distance Running Through Modified Play in Class V Students of SD Tunas Harapan Tanjung Anom Academic Year 2024/2025.